Prediction Method of Sealing Capacity Distribution of Regional Mudstone Caprocks Damaged by Fault During the Hydrocarbon Accumulation Period - Han, Xu; Fu, Guang; Liang, Mugui; Jin, Fengming; Han, Guomeng; Jiang, Wenya (Frontiers in Earth Science, 2022)
In order to study the distribution law of oil and gas above and below the regional mudstone caprocks damaged by fault in petroliferous basins, based on the study of the sealing mechanism and degree of regional mudstone caprocks damaged by fault during hydrocarbon accumulation period, the paleo-juxtaposition thickness of regional mudstone caprock was determined by determining the paleo-fault throw of faults and the paleo-thickness of regional mudstone caprocks during hydrocarbon accumulation period. According to the relation between the paleo-juxtaposition thickness of regional mudstone caprocks at known well points in the study area and the distribution of oil and gas above and below the regional mudstone caprock, the maximum juxtaposition thickness required for the upper and lower connection of fault-associated fracture zone in the regional mudstone caprock was determined. On this basis, a set of prediction methods for the sealing capacity of regional mudstone caprocks damaged by fault during hydrocarbon accumulation period was established. And then this method was applied to the prediction of the damage degree distribution of Zhangdong Fault to the regional mudstone caprock of E3s1M in the middle and late depositional period of N2m in Qikou Sag of Bohai Bay Basin during the hydrocarbon accumulation period. The results show that the damage degree of Zhangdong Fault to the regional mudstone caprock of E3s1M during the hydrocarbon accumulation period is large, the largest damage appears in the east, with a-value greater than 1, followed by the west, with a-value between 0.5 and 1; The relatively minor damage occurs to the middle west part, with a-value less than 0.5. The middle part is conducive to the accumulation and preservation of oil and gas generated from the source rock of E3s3, which is consistent with the fact that oil and gas discovered in E3s1L near Zhangdong Fault are mainly distributed in its middle part. It shows that this method is feasible to predict the damage degree distribution of regional mudstone caprocks during hydrocarbon accumulation period.